Implementation of the electronic-based government system (SPBE) in the north Sulawesi provincial government - Trisye Damopoli; Rizki Amalia; Frans Dione (Jurnal Scientia, 2024)
The information and communication technology (ICT) revolution provides opportunities for the government to innovate in the development of the state apparatus through the implementation of an Electronic-Based Government System (SPBE) or E-Government, namely where government administration utilizes ICT to provide services to government agencies, state civil servants, society and other parties. This research uses a qualitative approach with a descriptive method aimed at describing the object under study, in which there are efforts to observe, describe, record and analyze. The results and discussion of the Implementation of an Electronic-Based Government System (SPBE) in the North Sulawesi Provincial Government have not run optimally based on the research approach carried out through Indrajit's theory of Elements of Success in E-Government Development. This can be seen in the support element in the indicator of Regional Level Regulations/Regulations, where The SPBE architecture has not been created and only 6 SOPs out of 31 have been created.